2022
DOI: 10.5045/br.2021.2021152
|View full text |Cite
|
Sign up to set email alerts
|

IDH1/2 mutations in acute myeloid leukemia

Abstract: The mutational and epigenetic landscape of acute myeloid leukemia (AML) has become increasingly well understood in recent years, informing on biological targets for precision medicine. Among the most notable findings was the recognition of mutational hot-spots in the isocitrate dehydrogenase (IDH) genes. In this review, we provide an overview on the IDH1/2 mutation landscape in Korean AML patients, and compare it with available public data. We also discuss the role of IDH1/2 mutations as biomarkers and drug ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…A recent study found that patients with IDH1/IDH2 -mutated AML had favorable outcomes when treated with HMAs and venetoclax [ 34 ]. Our data may provide additional evidence to recommend HMAs combined with venetoclax or IDH1/ IDH2 inhibitors because it is difficult to expect improved survival with HMAs alone in elderly AML patients with IDH1/ IDH2 mutations [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that patients with IDH1/IDH2 -mutated AML had favorable outcomes when treated with HMAs and venetoclax [ 34 ]. Our data may provide additional evidence to recommend HMAs combined with venetoclax or IDH1/ IDH2 inhibitors because it is difficult to expect improved survival with HMAs alone in elderly AML patients with IDH1/ IDH2 mutations [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene panels target curated sets of genes associated with specific clinical phenotypes such as acute leukemia, MDS, and lymphoma. Sequencing aims to identify DNA SNVs that are confidently associated with the presenting disease [ 33 ]. NGS data allowed the detection of CNVs from targeted gene panels.…”
Section: Advances In Genomic Technologiesmentioning
confidence: 99%
“…Another area of research is the identification of genetic mutations in AML that can be targeted with precision medicine. Mutations in genes such as IDH1/2 have been identified in AML and have become targets for precision medicine approaches [29]. Additionally, pharmacogenomic profiling has been used to identify therapeutic vulnerabilities in pediatric AML, which can inform personalized treatment strategies [30].…”
Section: Recent Advances In the Treatment Of Acute Myeloid Leukemiamentioning
confidence: 99%